(3ObGFb GdEYQGHs - (3MjOQ HdG eQGO Hf CMeOs
(3ChdgG (B:s
... (3eYQa HGdCda hGddGe eQahY daXG hQaYg HGdVeI dCfg eYWha Ydi GdUdGI hGdYOd aj QaYg daXG YGed GdeYWha Ydjg (B.. (3Ydi YGed daX GdSeGYj MQa ef GdMQha GdLGQI ehVhYI (B...s
(3BNQgG (B:s
.. (3jLH GdQLhY aGdQO Ydi cd JbOjQjf (B.. (3Edjc aYdjc hGdSdGe Ydjc haj JQcjHg gcPG GdHGA eQahY daXG HCfg HOd ef SHYI YTQ hGdYGed aj QaYg daXG YGed GdeHOd efg (B. (3GdMeO ddg Ydi GdGJeGes
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdfMhs